Occurrence of Groundnut ringspot virus on Brazilian peanut crops - Camelo-Garcia, Viviana Marcela; Lima, Elison Fabricio B.; Mansilla-Cordova, Pedro Javier; Marques Rezende, Jorge Alberto; Kitajima, Elliot Watanabe; Barreto, Modesto [UNESP] (Springer, 2014)
A high incidence of plants with mosaic, chlorotic spots, ringspots, necrosis, smaller leaves, and stunting was observed on peanut crops (Arachis hypogaea L.) in Itapolis, So Paulo State, Brazil. Transmission electron microscope examination of thin sections of infected leaves revealed the presence of spheroidal particles, ca. 80 nm in diameter, suggestive of Tospovirus. A DNA fragment of similar to 600 bp was amplified by RT-PCR from total RNA extracted from infected tissues using primers specific for the nucleocapsid gene of Groundnut ringspot virus (GRSV). Nucleotide and deduced amino acid sequences of the fragments showed high identities with known GRSV isolates.
Keywords: Arachis hypogaea; Tospovirus; Frankliniella schultzei